A powder metallurgy transmission plate material for clutch and preparation method thereof
By using powder metallurgical transmission plate materials such as high-purity atomized iron powder and reinforcement, combined with specific preparation methods, the existing materials have been solved under high temperature and high stress conditions, and the comprehensive performance and service life of the materials have been significantly improved.
Patent Information
- Application Number
- CN202411920568.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing clutch transmission material has poor comprehensive performance under high temperature and high stress and other operating conditions, resulting in a shortened service life and may cause safety hazards.
A powder metallurgical transmission plate material including high-purity atomized iron powder, electrolytic copper powder, hydroxynickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano-silicon carbide particles, carbon fiber, whisker-like alumina, cellulose nanocrystals, rare earth oxides, lubricants and binders is used, and molded and sintered by specific preparation methods.
It significantly improves the overall performance of the transmission, including strength, hardness, wear resistance, thermal conductivity and corrosion resistance, ensuring reliability and durability in complex mechanical environments, extending service life and reducing safety risks.
Smart Images

Figure CN119346863B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of transmission plate materials, and in particular to a powder metallurgy transmission plate material for a clutch and a preparation method thereof. Background Art
[0002] With the continuous development of the vehicle industry and various mechanical transmission systems, the clutch, as a key component in the transmission system, has increasingly stringent performance requirements. Powder metallurgy transmission plates in the clutch have important functions such as transmitting torque, buffering impact, and ensuring smooth connection and disconnection of power. Therefore, the optimization and improvement of its performance has always been the focus of research in related fields.
[0003] In the field of traditional powder metallurgy transmission plate materials, more conventional metal powder formulas are mostly used, such as a certain proportion of iron powder with a small amount of other alloy element powders, supplemented by simple lubricants and binders. This traditional formula can meet basic usage requirements to a certain extent, but as the operating conditions of modern machinery become more complex, such as higher speeds, greater torque loads, and harsher working environments, its limitations are gradually becoming apparent. For example, the strength and hardness of existing materials are often difficult to maintain stability under high temperature and high stress conditions, and are prone to increased wear, deformation, and even failure, which not only affects the overall performance and service life of the clutch, but may also cause safety hazards.
[0004] In view of this, the art needs a powder metallurgy transmission plate material for a clutch and a preparation method thereof to solve the above problems. Summary of the invention
[0005] In order to solve the above technical problems, that is, to solve the problem that the existing clutch transmission plate materials have poor comprehensive performance under high temperature and high stress conditions, which affects the service life of the clutch and even causes safety hazards.
[0006] In one aspect, the present invention provides a powder metallurgy transmission plate material for a clutch, which comprises, in terms of mass percentage, 55%-65% high-purity atomized iron powder, 8%-12% electrolytic copper powder, 4%-8% hydroxy nickel powder, 1.5%-4% ferromolybdenum powder, 1%-3% chromium powder, 0.3%-1.5% lanthanum powder, 1.5%-3.5% nano-silicon carbide particles, 0.8%-2% carbon fiber, 0.5%-1.5% whisker-like aluminum oxide, 0.3%-1% cellulose nanocrystals, 0.5%-2% rare earth oxide, 2.3%-6% lubricant and 0.5%-1.8% binder.
[0007] In certain preferred embodiments, the lubricant includes 1.5%-3.5% flake graphite and 0.8%-2.5% nano molybdenum disulfide.
[0008] In certain preferred embodiments, the binder includes 0.3%-1% polyethylene glycol and 0.2%-0.8% sodium carboxymethyl cellulose.
[0009] In certain preferred embodiments, the rare earth oxide is yttrium oxide; or,
[0010] The rare earth oxide is cerium oxide; or,
[0011] The rare earth oxides include 0.4%-1.6% of cerium oxide and 0.1%-0.4% of yttrium oxide.
[0012] The powder metallurgy transmission plate material for clutch of the present invention has the following beneficial effects:
[0013] The high-purity atomized iron powder in the powder metallurgy transmission plate material for the clutch of the present invention serves as a basic component, providing a basic material skeleton and ensuring a certain strength and toughness foundation. Its large proportion ensures the stability of the overall structure. The electrolytic copper powder gives the material good thermal conductivity and electrical conductivity, which helps to dissipate heat in time during the operation of the clutch and ensure the stability of electrical signal transmission. It cooperates with iron powder to enhance the comprehensive physical properties of the material. Hydroxyl nickel powder effectively increases the strength and corrosion resistance of the material, so that the transmission plate can resist corrosion and maintain structural strength in complex environments. Molybdenum iron powder further improves the hardness and high-temperature performance of the material, so that the transmission plate can still maintain good mechanical properties under high-temperature conditions. It works together with chromium powder to enhance the material's wear resistance and corrosion resistance. The addition of lanthanum powder utilizes the characteristics of rare earth elements to refine the grains and enhance the uniformity and density of the material's internal structure, thereby improving the overall strength and Toughness, nano silicon carbide particles, whisker-like aluminum oxide and carbon fibers strengthen the material from different dimensions. Nano silicon carbide particles increase hardness and wear resistance, whisker-like aluminum oxide focuses on enhancing high temperature strength and wear resistance, and carbon fibers improve the strength and toughness of the material. The three complement each other and synergistically improve the mechanical properties of the material. While providing a certain strength and rigidity, cellulose nanocrystals can absorb lubricants and other additives with their special structure and adsorption properties, which helps to play a better lubricating role during the friction process and reduce the material density to achieve lightweight. Rare earth oxides are stable at high temperatures, can refine grains, inhibit grain growth and form a protective film, and improve the material's oxidation resistance and high temperature stability. Through the coordination of the above components and their proportions, the comprehensive performance of the clutch transmission plate is greatly improved, ensuring the reliability and durability of the transmission plate in a complex mechanical environment, increasing its service life and reducing safety risks.
[0014] On the other hand, the present invention also provides a method for preparing the above-mentioned powder metallurgy transmission plate material for clutch, the preparation method comprising:
[0015] S1: Pretreatment of high purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, carbon fiber, and cellulose nanocrystals;
[0016] S2: adding the pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose into a high-speed mixer for primary mixing, then adding flake graphite, nano molybdenum disulfide and whisker-like aluminum oxide into the mixture mixed once in the high-speed mixer for secondary mixing, and then adding carbon fiber and cellulose nanocrystals into the mixture mixed twice in the high-speed mixer for tertiary mixing;
[0017] S3: molding the three-mixed mixture by bidirectional pressing;
[0018] S4: performing low-temperature pre-sintering and high-temperature sintering on the formed material in sequence;
[0019] S5: Machining, surface treatment and heat treatment of the sintered material.
[0020] In some preferred embodiments, step S1 specifically includes:
[0021] S11: vacuum drying the high-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, ferromolybdenum powder, chromium powder and lanthanum powder respectively at a drying temperature of 110-130° C. for 5-7 hours;
[0022] S12: soaking the nano-silicon carbide particles in a composite treatment agent of a silane coupling agent and a titanate coupling agent, stirring evenly and then performing ultrasonic treatment for 3-5 hours at a temperature of 60-80° C., and then drying at 80-100° C. for 4-6 hours;
[0023] S13: After the carbon fiber is chopped, it is immersed in a dopamine solution, the concentration of the dopamine solution is 1-3 g / L, the pH value is 8-9, and the reaction is stirred at room temperature for 12-24 hours, and then the carbon fiber is taken out, rinsed with deionized water, and dried at 60-80° C. for 3-5 hours;
[0024] S14: Dispersing cellulose nanocrystals in a silane coupling agent, ultrasonically treating for 2-4 hours, and then filtering and drying.
[0025] In certain preferred embodiments, in step S2, during the first mixing process, stirring and mixing are performed at 60-80°C for 1-2 hours, during the second mixing process, stirring and mixing are performed for 1-2 hours, and during the third mixing process, stirring and mixing are performed for 1-2 hours, wherein the first mixing, the second mixing and the third mixing are all combined with ultrasonic assisted mixing.
[0026] In some preferred embodiments, step S3 specifically includes:
[0027] S31: The mixed powder is loaded into a mold and pre-pressed at a pressure of 200-300 MPa, a holding time of 5-10 seconds, and a pressing speed of 5-10 mm / s;
[0028] S32: The pre-pressed material is subjected to bidirectional pressing at a pressure of 600-900 MPa, a holding time of 15-25 seconds, and a pressing speed of 3-8 mm / s. During the bidirectional pressing process, the mold is heated to 100-150°C at a heating rate of 15-25°C / min.
[0029] In some preferred embodiments, step S4 specifically includes:
[0030] S41: The formed material is placed in a vacuum of 1×10 -3 -1×10 -2 Low temperature pre-sintering is carried out under vacuum conditions of 1000 Pa, the temperature is 800-1000°C, the time is 1-2 hours, and the heating rate is 10-20°C / min;
[0031] S42: placing the pre-sintered material in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering at a temperature of 1200-1400°C for 2-3 hours at a heating rate of 15-25°C / minute, wherein microwave assisted sintering is adopted during the high-temperature sintering process, the microwave frequency is 2.45 GHz, and the microwave power is 5-10 kW.
[0032] In some preferred embodiments, step S5 specifically includes:
[0033] S51: Mechanically process the sintered material;
[0034] S52: The machined material is first subjected to phosphating treatment at a temperature of 50-70°C for 20-30 minutes and a phosphating solution spraying pressure of 0.1-0.3MPa. The phosphating solution formula is: 20-30g / L zinc dihydrogen phosphate, 50-70g / L zinc nitrate and 1-3g / L sodium fluoride, with a pH value of 2-3;
[0035] S53: electroplating copper or chemical copper plating is performed on the phosphating material. When electroplating copper is used, the current density is 1-3A / dm², the electroplating time is 10-30 minutes, and when chemical copper plating is used, the plating solution temperature is 40-60°C, and the deposition rate is 2-5μm / h;
[0036] S54: heat-treating the material under nitrogen protection, heating to 200-300°C at a heating rate of 10-20°C / min, keeping the temperature for 1-2 hours, and then slowly cooling to room temperature at a cooling rate of 5-10°C / min.
[0037] The preparation method of the powder metallurgy transmission plate material for clutch of the present invention has the following beneficial effects:
[0038] The present invention first pre-treats each key raw material, that is, vacuum drying the metal powder to remove moisture and gas to avoid defects in subsequent processing. The multi-step mixing process of step S2 is carried out step by step. First, the metal powder, key reinforcing particles and rare earth oxides are mixed with a binder to make the basic components and important additives initially and evenly combined and the structure is initially stabilized by the binder. Then, flake graphite, nano molybdenum disulfide and whisker-like aluminum oxide are added to further enrich the material performance components and mix them evenly again. Finally, carbon fiber and cellulose nanocrystals are added to ensure that each special reinforcing component is evenly dispersed in the system. By gradually increasing the stirring speed and ultrasonic-assisted mixing, the sufficiency and uniformity of the mixing are guaranteed, so that a good synergistic system is formed between the components. In addition, the use of a two-way pressing method can make the density of the green body more uniform, which ensures the material from the molding link. In order to ensure the consistency and stability of performance and avoid local performance differences caused by uneven density, a two-stage sintering process is adopted. Low-temperature pre-sintering removes organic matter and adsorbed gases to make the material initially densified. High-temperature sintering in a specific atmosphere promotes the full fusion of metal powders to form a dense metallurgical bond. Microwave-assisted sintering technology improves the sintering speed and uniformity, ensuring that the material forms a stable and high-performance organizational morphology in the microstructure. Composite surface treatment technology is used for surface treatment after machining. Phosphating treatment improves corrosion resistance and wear resistance, copper plating further improves conductivity and corrosion resistance, and heat treatment improves the performance stability of the material. Each post-processing step acts in sequence to optimize the transmission plate in all aspects from macroscopic appearance to surface performance to overall performance stability, so that the final prepared powder metallurgy transmission plate for clutch meets the high-performance and high-reliability requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings:
[0040] Figure 1 The present invention is a flow chart of the method for preparing the powder metallurgy transmission plate material for clutch. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0042] Based on the problem pointed out in the background technology that the existing clutch transmission plate materials have poor comprehensive performance under high temperature and high stress conditions, which affects the service life of the clutch and even causes safety hazards, the present invention provides a powder metallurgy transmission plate material for a clutch and a preparation method thereof, aiming to greatly improve the comprehensive performance of the clutch transmission plate, ensure the reliability and durability of the transmission plate in a complex mechanical environment, increase the service life and reduce safety risks.
[0043] The powder metallurgy transmission plate material for the clutch of the present invention comprises, by mass percentage, 55%-65% high-purity atomized iron powder, 8%-12% electrolytic copper powder, 4%-8% hydroxy nickel powder, 1.5%-4% ferromolybdenum powder, 1%-3% chromium powder, 0.3%-1.5% lanthanum powder, 1.5%-3.5% nano silicon carbide particles, 0.8%-2% carbon fiber, 0.5%-1.5% whisker-like aluminum oxide, 0.3%-1% cellulose nanocrystals, 0.5%-2% rare earth oxide, 2.3%-6% lubricant and 0.5%-1.8% binder; wherein the purity of the high-purity atomized iron powder is preferably greater than or equal to 99%.
[0044] Preferably, the lubricant includes 1.5%-3.5% of flake graphite and 0.8%-2.5% of nano molybdenum disulfide; the binder includes 0.3%-1% of polyethylene glycol and 0.2%-0.8% of sodium carboxymethyl cellulose.
[0045] The rare earth oxide may be only yttrium oxide or only cerium oxide. Of course, it is preferred to use a mixture of cerium oxide and yttrium oxide. More preferably, the rare earth oxide includes 0.4%-1.6% of cerium oxide and 0.1%-0.4% of yttrium oxide.
[0046] In the powder metallurgy transmission plate material for the clutch of the present invention, high-purity atomized iron powder is used as the main matrix component, which provides the transmission plate with a basic structural skeleton and a certain strength foundation. Its good formability enables other components to be effectively combined with it and jointly construct a stable material structure; the electrolytic copper powder in the material can not only quickly conduct the heat generated when the clutch is working and ensure good electrical signal transmission by virtue of its own excellent thermal conductivity and electrical conductivity, but also can form alloys or intermetallic compounds with iron powder during the sintering process, enhance the strength and hardness of the material through solid solution strengthening, and improve toughness at the same time, and cooperate with iron powder to lay the foundation for the mechanical and physical properties of the material; hydroxy nickel powder increases the strength and corrosion resistance of the material , working together with other metal powders to further improve the durability of the material under complex working conditions. It is evenly distributed in the iron powder matrix and works together with the electrolytic copper powder to enhance the material's resistance to environmental factors, ensuring the stability of the structure and performance of the transmission plate during long-term use; molybdenum iron powder improves the material's hardness and high-temperature performance, and works together with chromium powder to significantly improve the material's wear and corrosion resistance. Especially in the high-temperature and high-friction clutch working environment, the reinforcing phase formed by molybdenum iron powder and chromium powder can effectively prevent wear and oxidation on the material surface, and combined with the matrix structure of high-purity atomized iron powder, it enhances the stability of the overall material under extreme conditions; the addition of rare earth element lanthanum powder can refine the grains and enhance the uniformity of the material's internal structure It interacts with other metal powders to optimize the crystal structure of the material, making the stress distribution of the material more uniform when subjected to external force, improving the overall strength and toughness, and synergistically improving the comprehensive mechanical properties of the material; after the nano-silicon carbide particles are evenly dispersed inside the material, they can effectively improve the overall hardness and wear resistance, and synergize with the whisker-like alumina. The whisker structure of the whisker-like alumina can effectively prevent the expansion of cracks. The combination of the two further enhances the wear resistance of the material, and can maintain a stable strengthening effect under high temperature conditions, and together with the metal powder matrix, a high-strength, high-wear-resistant and high-temperature resistant material system is constructed; carbon fiber works synergistically with nano-silicon carbide particles, whisker-like alumina and other reinforcing agents when the material is subjected to When external force is applied, the stress is dispersed to other reinforcing components through its own load-bearing and stress transfer function, thus jointly improving the material's impact resistance and mechanical performance stability; cellulose nanocrystals can provide the material with certain strength and rigidity, and its special structure and adsorption can absorb lubricants such as flake graphite and nano-molybdenum disulfide, thus playing a better lubricating role in the friction process, reducing wear and reducing material density to achieve lightweight, and together with other reinforcing agents, optimizing the comprehensive performance of the material, so that it achieves a balance in mechanical properties, wear resistance and lightweight; flake graphite provides good self-lubricating properties, and nano-molybdenum disulfide reduces the friction coefficient. The combined effect of the two significantly reduces the friction and wear of the transmission plate during operation;At the same time, the flake structure of flake graphite is conducive to the formation of a lubricating film during the friction process, and the nano-scale particles of nano-molybdenum disulfide can better fill the pores and enhance the density of the material. They work together with cellulose nanocrystals to further enhance the lubrication effect and structural stability of the material; polyethylene glycol helps the molding and pressing of the powder, improves the density and uniformity of the material, and sodium carboxymethyl cellulose enhances the bonding of the material and improves the strength after molding; the combination of the two ensures that the components are closely combined during the powder molding process, so that the mixed powder can form a stable green body structure, providing a good foundation for subsequent sintering and other processes, and ensuring the final performance reliability and consistency of the transmission plate. ;
[0047] In addition, after repeated experiments, analysis and comparison by the inventors, it was found that during the sintering process of the material, cerium oxide and yttrium oxide can play a pinning role at the grain boundaries. These rare earth oxide particles will be adsorbed on the growing grain boundaries, and yttrium oxide will interact with iron powder atoms at the grain boundaries. Since the atomic size and chemical properties of rare earth oxides are different from those of iron powder atoms, they will hinder the normal migration of grain boundaries. When the grains try to grow, the movement of the grain boundaries will be hindered by these adsorbed rare earth oxide particles, just like setting up obstacles at the grain boundaries, thereby inhibiting the excessive growth of the grains. Cerium oxide and yttrium oxide can also serve as cores for heterogeneous nucleation; during the solidification or recrystallization process of the material, atoms need to gather on certain cores to form new grains; the presence of rare earth oxide particles provides additional nucleation sites for metal atoms; the surface energy and crystal structure of these particles are different from those of the metal matrix, making it easier for metal atoms to gather and nucleate on their surfaces. The crystal structure of cerium oxide forms a A certain lattice mismatch will cause the surrounding metal atoms to deposit on its surface in a certain orientation to form new grains, thereby increasing the number of grains and achieving the effect of refining the grains; under high temperature environment, cerium oxide and yttrium oxide can form a dense protective film on the surface of the material; there is a chemical bond between the oxygen atoms in the rare earth oxides and the metal atoms (such as iron atoms); under high temperature and oxygen environment, the oxygen atoms in cerium oxide and yttrium oxide will react with the metal atoms on the surface of the material to preferentially form an oxide protective film; cerium oxide will form a composite oxide film containing cerium, oxygen and other metal elements (such as iron, chromium, etc.) on the surface of the material; the structure of this film is dense and can prevent oxygen molecules from further diffusing into the interior of the material; rare earth oxides can also adjust the oxidation state of the material surface through redox reactions; at high temperatures, when the metal atoms on the surface of the material begin to oxidize, cerium oxide and yttrium oxide can provide or accept electrons to control the rate of the oxidation reaction; cerium oxide can 3+ and Ce 4+ When metal atoms (such as iron) on the surface of the material are oxidized to Fe 2+ or Fe 3+ When Ce4+ Can accept electrons and be reduced to Ce 3+ , thereby inhibiting the excessive oxidation of metal atoms and maintaining the chemical stability of the material surface; during the sintering process, cerium oxide and yttrium oxide will be distributed between metal grains, and their presence can change the sintering behavior of metal powders; on the one hand, by refining the grains, the metal powders are more tightly bonded; between iron powder particles, the rare earth oxides refine the grains, increasing the contact area between the iron powders and making the sintering neck grow more uniformly, thereby improving the density of the material; on the other hand, it can react with impurity elements in metal powders to purify the microstructure of the material. Cerium oxide can react with a small amount of impurity elements such as sulfur and phosphorus in metal powders to generate stable compounds, reducing the effects of these impurities on the material. The invention discloses a novel nano-silicon carbide particle structure, which can be used to prepare a composite material of the present invention and to prepare a composite material of the present invention. The invention discloses a ...
[0048] like Figure 1 As shown, the preparation method of the powder metallurgy transmission plate material for the clutch of the present invention comprises:
[0049] S1: Pretreatment of high purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, carbon fiber, and cellulose nanocrystals;
[0050] In a preferred embodiment, the above step S1 specifically includes:
[0051] S11: vacuum drying high-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder respectively to remove moisture and adsorbed gas, the drying temperature is 110-130°C, the drying time is 5-7 hours, the heating rate is controlled at 25-35°C / hour to avoid powder agglomeration, and then the above metal powders are respectively ball-milled, the ball-milling medium is stainless steel balls, the ball-to-material ratio is 5:1-8:1, the ball-milling time is 10-15 hours, the ball-milling speed is 200-300 rpm, and an appropriate amount of ethanol or acetone is added as a dispersant, and the amount of the dispersant is 0.5%-1.5% of the mass of each metal powder;
[0052] S12: immersing the nano-silicon carbide particles in a composite treatment agent of a silane coupling agent and a titanate coupling agent, wherein the concentration of the treatment agent solution is 2%-5%, stirring the mixture evenly, and then performing ultrasonic treatment, wherein the ultrasonic frequency is 20-40kHz, the treatment time is 3-5 hours, the temperature is 60-80°C, and then drying the mixture at 80-100°C for 4-6 hours;
[0053] S13: After the carbon fiber is chopped, it is immersed in a dopamine solution, the concentration of the dopamine solution is 1-3 g / L, the pH value is 8-9, and the reaction is stirred at room temperature for 12-24 hours, and then the carbon fiber is taken out, rinsed with deionized water, and dried at 60-80° C. for 3-5 hours;
[0054] S14: Disperse the cellulose nanocrystals in a solution containing 1%-3% silane coupling agent, ultrasonically treat for 2-4 hours at an ultrasonic power of 300-500 W, and then filter and dry at 60-80° C. for 3-5 hours.
[0055] S2: adding the pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose into a high-speed mixer for primary mixing, then adding flake graphite, nano molybdenum disulfide and whisker-like aluminum oxide into the mixture mixed once in the high-speed mixer for secondary mixing, and then adding carbon fiber and cellulose nanocrystals into the mixture mixed twice in the high-speed mixer for tertiary mixing;
[0056] In a preferred embodiment, in the above step S2, during the first mixing process, stirring and mixing are carried out at 60-80°C for 1-2 hours, and the initial stirring speed is 500-800 rpm, which is gradually increased to 1000-1500 rpm. During the second mixing process, stirring and mixing are carried out for 1-2 hours at a stirring speed of 1200-1800 rpm. During the third mixing process, stirring and mixing are carried out for 1-2 hours at a stirring speed of 1500-2000 rpm, wherein the first mixing, the second mixing and the third mixing are all combined with ultrasonic assisted mixing.
[0057] S3: molding the three-mixed mixture by bidirectional pressing;
[0058] In a preferred embodiment, step S3 specifically includes:
[0059] S31: The mixed powder is loaded into a mold and pre-pressed at a pressure of 200-300 MPa, a holding time of 5-10 seconds, and a pressing speed of 5-10 mm / s;
[0060] S32: performing bidirectional pressing on the pre-pressed material, with a pressure of 600-900 MPa, a holding time of 15-25 seconds, and a pressing speed of 3-8 mm / s, wherein during the bidirectional pressing process, the mold is heated to 100-150° C., and a heating rate of 15-25° C. / min;
[0061] Further preferably, an electromagnetic coil that can generate a strong magnetic field is surrounded around the mold, and pre-pressing is performed while applying the magnetic field. The magnetic field strength can be controlled between 0.5-2 Tesla, the pre-pressing pressure is 100-200 MPa, and the holding time is 3-5 seconds. Then, bidirectional pressing is performed under the continuous action of the magnetic field, and the pressing pressure is 600-900 MPa, and the holding time is 15-25 seconds. For metal powders in powder metallurgy materials (such as high-purity atomized iron powder, electrolytic copper powder, etc.), under the action of the magnetic field, the electrons inside them will move in a directional manner, resulting in a certain magnetization of the powder particles. The magnetized powder particles will be arranged along the direction of the magnetic field, so that the material forms a certain preferential orientation during the molding process. This preferential orientation can improve the mechanical properties of the material in a specific direction, such as improving the strength and hardness of the material in the direction of the magnetic field. At the same time, the presence of the magnetic field can also promote the enhanced interaction between the metal powder and other additives (such as rare earth oxides, nano-silicon carbide particles, etc.), because the magnetic field will affect the distribution of electron clouds around these particles, making them more closely combined, thereby improving the overall performance of the material.
[0062] S4: performing low-temperature pre-sintering and high-temperature sintering on the formed material in sequence;
[0063] In a preferred embodiment, step S4 specifically includes:
[0064] S41: The formed material is placed in a vacuum of 1×10 -3 -1×10 -2 Low temperature pre-sintering is carried out under vacuum conditions of 1000 Pa, the temperature is 800-1000°C, the time is 1-2 hours, and the heating rate is 10-20°C / min;
[0065] S42: The pre-sintered material is placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 8%-12%, a sintering temperature of 1200-1400°C, a sintering time of 2-3 hours, and a heating rate of 15-25°C / minute. During the high-temperature sintering process, microwave assisted sintering is adopted, the microwave frequency is 2.45GHz, and the microwave power is 5-10kW.
[0066] S5: Machining, surface treatment and heat treatment of the sintered material.
[0067] In a preferred embodiment, step S5 specifically includes:
[0068] S51: Mechanical processing of the sintered material, such as grinding, polishing, etc., using low-stress processing methods, grinding speed of 10-20 m / s, feed rate of 0.05-0.15 mm / rev, to achieve the required size and surface accuracy;
[0069] S52: The machined material is first subjected to phosphating treatment at a temperature of 50-70°C for 20-30 minutes and a phosphating solution spraying pressure of 0.1-0.3MPa. The phosphating solution formula is: 20-30g / L zinc dihydrogen phosphate, 50-70g / L zinc nitrate and 1-3g / L sodium fluoride, with a pH value of 2-3;
[0070] S53: electroplating copper or chemical copper plating is performed on the phosphating material. When electroplating copper is used, the current density is 1-3A / dm², the electroplating time is 10-30 minutes, and when chemical copper plating is used, the plating solution temperature is 40-60°C, and the deposition rate is 2-5μm / h;
[0071] S54: heat-treating the material under nitrogen protection, heating to 200-300°C at a heating rate of 10-20°C / min, keeping the temperature for 1-2 hours, and then slowly cooling to room temperature at a cooling rate of 5-10°C / min.
[0072] The technical solution of the present invention is further described below in conjunction with a plurality of embodiments and comparative examples.
[0073] Embodiment 1
[0074] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 65% high-purity atomized iron powder, 12% electrolytic copper powder, 7% hydroxy nickel powder, 3% ferromolybdenum powder, 2% chromium powder, 0.5% lanthanum powder, 1.5% nano silicon carbide particles, 1% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0075] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0076] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 120°C for 6 hours and the heating rate was controlled at 30°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 6:1, the ball milling time was 12 hours, the ball milling speed was 250 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 1% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 3%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 30kHz, the treatment time was 4 hours, the temperature was 70°C, and then dried at 90°C for 5 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 2 g / L and a pH value of 8.5. The reaction was stirred at room temperature for 18 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 70°C for 4 hours. Cellulose nanocrystals were dispersed in a solution containing 2% silane coupling agent, with an ultrasonic power of 400 W, and ultrasonically treated for 3 hours, then filtered and dried at 70°C for 4 hours.
[0077] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for one ultrasonic mixing. During the one ultrasonic mixing process, the mixture is stirred and mixed at 70°C for 1.5 hours, and the stirring speed is initially 600 rpm and gradually increased to 1200 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the one ultrasonic mixing in the high-speed mixer for a second ultrasonic mixing. During the second ultrasonic mixing process, the mixture is stirred and mixed for 1.5 hours at a stirring speed of 1500 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the second ultrasonic mixing in the high-speed mixer for a third ultrasonic mixing. During the third ultrasonic mixing process, the mixture is stirred and mixed for 1.5 hours at a stirring speed of 1800 rpm.
[0078] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 1 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 250 MPa, a holding time of 8 seconds, and a pressing speed of 8 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 700 MPa, a holding time of 20 seconds, and a pressing speed of 5 mm / s. During the bidirectional pressing process, the mold is heated to 120°C at a heating rate of 20°C / min.
[0079] The formed material is placed in a vacuum of 5×10 -3Low-temperature pre-sintering was carried out under vacuum conditions of 100 Pa, at a temperature of 900°C, for 1.5 hours, and a heating rate of 15°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 10%, a sintering temperature of 1300°C, a sintering time of 2.5 hours, and a heating rate of 20°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 8 kW.
[0080] The sintered material was ground and polished using a low stress machining method with a grinding speed of 15 m / s and a feed rate of 0.1 mm / rev to achieve the required size and surface accuracy. The machined material was first phosphated at a temperature of 60°C for 25 minutes and a phosphating solution spray pressure of 0.2 MPa. The phosphating solution formula was 25 g / L zinc dihydrogen phosphate, 60 g / L zinc nitrate and 2 g / L sodium fluoride, with a pH value of 2.5. The phosphated material was electroplated with copper at a current density of 2 A / dm² and an electroplating time of 20 minutes. The material was heat treated under nitrogen protection at a heating rate of 15°C / min to 250°C for 1.5 hours, and then slowly cooled to room temperature at a cooling rate of 8°C / min.
[0081] Embodiment 2
[0082] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 65% high-purity atomized iron powder, 12% electrolytic copper powder, 7% hydroxy nickel powder, 3% ferromolybdenum powder, 2% chromium powder, 0.5% lanthanum powder, 1.5% nano silicon carbide particles, 1% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0083] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0084] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 110°C for 5 hours and the heating rate was controlled at 25°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 5:1, the ball milling time was 10 hours, the ball milling speed was 200 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 0.5% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 2%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 20kHz, the treatment time was 3 hours, the temperature was 60°C, and then dried at 80°C for 4 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 1 g / L and a pH of 8. The reaction was stirred at room temperature for 12 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 60°C for 3 hours. Cellulose nanocrystals were dispersed in a solution containing 1% silane coupling agent, and the ultrasonic power was 300 W for 2 hours, and then filtered and dried at 60°C for 3 hours.
[0085] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for primary ultrasonic mixing. During the primary ultrasonic mixing, the mixture is stirred and mixed at 60°C for 1 hour, and the stirring speed is initially 500 rpm and gradually increased to 1000 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the primary ultrasonic mixing in the high-speed mixer for secondary ultrasonic mixing. During the secondary ultrasonic mixing, the mixture is stirred and mixed for 1 hour at a stirring speed of 1200 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the secondary ultrasonic mixing in the high-speed mixer for tertiary ultrasonic mixing. During the tertiary ultrasonic mixing, the mixture is stirred and mixed for 1 hour at a stirring speed of 1500 rpm.
[0086] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 0.5 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 200 MPa, a holding time of 5 seconds, and a pressing speed of 5 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 600 MPa, a holding time of 15 seconds, and a pressing speed of 3 mm / s. During the bidirectional pressing process, the mold is heated to 100°C at a heating rate of 15°C / min.
[0087] The formed material is placed in a vacuum of 1×10 -3Low-temperature pre-sintering was carried out under vacuum conditions of 100 Pa, at a temperature of 800°C, for 1 hour, and a heating rate of 10°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 8%, a sintering temperature of 1200°C, a sintering time of 2 hours, and a heating rate of 15°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 5 kW.
[0088] The sintered material is ground and polished using a low stress processing method with a grinding speed of 10 m / s and a feed rate of 0.05 mm / rev to achieve the required size and surface accuracy; the machined material is first phosphated at a temperature of 50°C for 20 minutes and a phosphating solution spray pressure of 0.1 MPa, wherein the phosphating solution formula is: 20 g / L zinc dihydrogen phosphate, 50 g / L zinc nitrate and 1 g / L sodium fluoride, with a pH value of 2; the phosphated material is subjected to chemical copper plating at a bath temperature of 40°C and a deposition rate of 2 μm / h; the material is heat treated under nitrogen protection, heated to 200°C at a heating rate of 10°C / min, kept warm for 1 hour, and then slowly cooled to room temperature at a cooling rate of 5°C / min.
[0089] Embodiment 3
[0090] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 65% high-purity atomized iron powder, 12% electrolytic copper powder, 7% hydroxy nickel powder, 3% ferromolybdenum powder, 2% chromium powder, 0.5% lanthanum powder, 1.5% nano silicon carbide particles, 1% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0091] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0092] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 130°C for 7 hours and the heating rate was controlled at 35°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 8:1, the ball milling time was 15 hours, the ball milling speed was 300 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 1.5% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 5%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 40kHz, the treatment time was 5 hours, the temperature was 80°C, and then dried at 100°C for 6 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 3 g / L and a pH of 9. The reaction was stirred at room temperature for 24 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 80°C for 5 hours. Cellulose nanocrystals were dispersed in a solution containing 3% silane coupling agent, with an ultrasonic power of 500 W, and ultrasonically treated for 4 hours, then filtered and dried at 80°C for 5 hours.
[0093] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for primary ultrasonic mixing. During the primary ultrasonic mixing, the mixture is stirred and mixed at 80°C for 2 hours, and the stirring speed is initially 800 rpm and gradually increased to 1500 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the primary ultrasonic mixing in the high-speed mixer for secondary ultrasonic mixing. During the secondary ultrasonic mixing, the mixture is stirred and mixed for 2 hours at a stirring speed of 1800 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the secondary ultrasonic mixing in the high-speed mixer for tertiary ultrasonic mixing. During the tertiary ultrasonic mixing, the mixture is stirred and mixed for 2 hours at a stirring speed of 2000 rpm.
[0094] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 2 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 300 MPa, a holding time of 10 seconds, and a pressing speed of 10 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 900 MPa, a holding time of 25 seconds, and a pressing speed of 8 mm / s. During the bidirectional pressing process, the mold is heated to 150°C at a heating rate of 25°C / min.
[0095] The formed material is placed in a vacuum of 1×10 -2Low-temperature pre-sintering was carried out under vacuum conditions of 1000°C, with a temperature of 1000°C, a time of 2 hours, and a heating rate of 20°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 12%, a sintering temperature of 1400°C, a sintering time of 3 hours, and a heating rate of 25°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 10 kW.
[0096] The sintered material was ground and polished using a low stress machining method with a grinding speed of 20 m / s and a feed rate of 0.15 mm / rev to achieve the required size and surface accuracy. The machined material was first phosphated at a temperature of 70°C for 30 minutes and a phosphating solution spray pressure of 0.3 MPa. The phosphating solution formula was 30 g / L zinc dihydrogen phosphate, 70 g / L zinc nitrate and 3 g / L sodium fluoride, with a pH value of 3. The phosphated material was electroplated with copper at a current density of 3A / dm² for 30 minutes. The material was heat treated under nitrogen protection, heated to 300°C at a heating rate of 20°C / min, kept at this temperature for 2 hours, and then slowly cooled to room temperature at a cooling rate of 10°C / min.
[0097] Embodiment 4
[0098] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 60% high-purity atomized iron powder, 10% electrolytic copper powder, 8% hydroxy nickel powder, 4% ferromolybdenum powder, 3% chromium powder, 1.5% lanthanum powder, 3.5% nano silicon carbide particles, 2% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0099] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0100] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 120°C for 6 hours and the heating rate was controlled at 30°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 6:1, the ball milling time was 12 hours, the ball milling speed was 250 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 1% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 3%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 30kHz, the treatment time was 4 hours, the temperature was 70°C, and then dried at 90°C for 5 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 2 g / L and a pH value of 8.5. The reaction was stirred at room temperature for 18 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 70°C for 4 hours. Cellulose nanocrystals were dispersed in a solution containing 2% silane coupling agent, with an ultrasonic power of 400 W, and ultrasonically treated for 3 hours, then filtered and dried at 70°C for 4 hours.
[0101] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for one ultrasonic mixing. During the one ultrasonic mixing process, the mixture is stirred and mixed at 70°C for 1.5 hours, and the stirring speed is initially 600 rpm and gradually increased to 1200 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the one ultrasonic mixing in the high-speed mixer for a second ultrasonic mixing. During the second ultrasonic mixing process, the mixture is stirred and mixed for 1.5 hours at a stirring speed of 1500 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the second ultrasonic mixing in the high-speed mixer for a third ultrasonic mixing. During the third ultrasonic mixing process, the mixture is stirred and mixed for 1.5 hours at a stirring speed of 1800 rpm.
[0102] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 1 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 250 MPa, a holding time of 8 seconds, and a pressing speed of 8 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 700 MPa, a holding time of 20 seconds, and a pressing speed of 5 mm / s. During the bidirectional pressing process, the mold is heated to 120°C at a heating rate of 20°C / min.
[0103] The formed material is placed in a vacuum of 5×10 -3Low-temperature pre-sintering was carried out under vacuum conditions of 100 Pa, at a temperature of 900°C, for 1.5 hours, and a heating rate of 15°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 10%, a sintering temperature of 1300°C, a sintering time of 2.5 hours, and a heating rate of 20°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 8 kW.
[0104] The sintered material was ground and polished using a low stress machining method with a grinding speed of 15 m / s and a feed rate of 0.1 mm / rev to achieve the required size and surface accuracy. The machined material was first phosphated at a temperature of 60°C for 25 minutes and a phosphating solution spray pressure of 0.2 MPa. The phosphating solution formula was 25 g / L zinc dihydrogen phosphate, 60 g / L zinc nitrate and 2 g / L sodium fluoride, with a pH value of 2.5. The phosphated material was electroplated with copper at a current density of 2 A / dm² and an electroplating time of 20 minutes. The material was heat treated under nitrogen protection at a heating rate of 15°C / min to 250°C for 1.5 hours, and then slowly cooled to room temperature at a cooling rate of 8°C / min.
[0105] Embodiment 5
[0106] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 60% high-purity atomized iron powder, 10% electrolytic copper powder, 8% hydroxy nickel powder, 4% ferromolybdenum powder, 3% chromium powder, 1.5% lanthanum powder, 3.5% nano silicon carbide particles, 2% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0107] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0108] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 110°C for 5 hours and the heating rate was controlled at 25°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 5:1, the ball milling time was 10 hours, the ball milling speed was 200 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 0.5% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 2%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 20kHz, the treatment time was 3 hours, the temperature was 60°C, and then dried at 80°C for 4 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 1 g / L and a pH of 8. The reaction was stirred at room temperature for 12 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 60°C for 3 hours. Cellulose nanocrystals were dispersed in a solution containing 1% silane coupling agent, and the ultrasonic power was 300 W for 2 hours, and then filtered and dried at 60°C for 3 hours.
[0109] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for primary ultrasonic mixing. During the primary ultrasonic mixing, the mixture is stirred and mixed at 60°C for 1 hour, and the stirring speed is initially 500 rpm and gradually increased to 1000 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the primary ultrasonic mixing in the high-speed mixer for secondary ultrasonic mixing. During the secondary ultrasonic mixing, the mixture is stirred and mixed for 1 hour at a stirring speed of 1200 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the secondary ultrasonic mixing in the high-speed mixer for tertiary ultrasonic mixing. During the tertiary ultrasonic mixing, the mixture is stirred and mixed for 1 hour at a stirring speed of 1500 rpm.
[0110] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 0.5 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 200 MPa, a holding time of 5 seconds, and a pressing speed of 5 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 600 MPa, a holding time of 15 seconds, and a pressing speed of 3 mm / s. During the bidirectional pressing process, the mold is heated to 100°C at a heating rate of 15°C / min.
[0111] The formed material is placed in a vacuum of 1×10 -3Low-temperature pre-sintering was carried out under vacuum conditions of 100 Pa, at a temperature of 800°C, for 1 hour, and a heating rate of 10°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 8%, a sintering temperature of 1200°C, a sintering time of 2 hours, and a heating rate of 15°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 5 kW.
[0112] The sintered material is ground and polished using a low stress processing method with a grinding speed of 10 m / s and a feed rate of 0.05 mm / rev to achieve the required size and surface accuracy; the machined material is first phosphated at a temperature of 50°C for 20 minutes and a phosphating solution spray pressure of 0.1 MPa, wherein the phosphating solution formula is: 20 g / L zinc dihydrogen phosphate, 50 g / L zinc nitrate and 1 g / L sodium fluoride, with a pH value of 2; the phosphated material is subjected to chemical copper plating at a bath temperature of 40°C and a deposition rate of 2 μm / h; the material is heat treated under nitrogen protection, heated to 200°C at a heating rate of 10°C / min, kept warm for 1 hour, and then slowly cooled to room temperature at a cooling rate of 5°C / min.
[0113] Embodiment 6
[0114] The powder metallurgy transmission plate materials for clutch include, by mass percentage: 60% high-purity atomized iron powder, 10% electrolytic copper powder, 8% hydroxy nickel powder, 4% ferromolybdenum powder, 3% chromium powder, 1.5% lanthanum powder, 3.5% nano silicon carbide particles, 2% carbon fiber, 1.2% whisker-like aluminum oxide, 0.8% cellulose nanocrystals, 0.8% cerium oxide, 0.2% yttrium oxide, 2.5% flake graphite, 1.5% nano molybdenum disulfide, 0.6% polyethylene glycol and 0.4% sodium carboxymethyl cellulose.
[0115] The preparation method of the above-mentioned powder metallurgy transmission plate material for clutch comprises:
[0116] High-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, molybdenum iron powder, chromium powder and lanthanum powder were vacuum dried at 130°C for 7 hours and the heating rate was controlled at 35°C / hour. Then the above metal powders were ball milled, stainless steel balls were used as the ball milling medium, the ball-to-material ratio was 8:1, the ball milling time was 15 hours, the ball milling speed was 300 rpm, and an appropriate amount of ethanol or acetone was added as a dispersant, and the amount of dispersant was 1.5% of the mass of each metal powder. Nano-silicon carbide particles were immersed in a composite treatment agent of silane coupling agent and titanate coupling agent, the concentration of the treatment agent solution was 5%, and ultrasonic treatment was performed after stirring evenly, the ultrasonic frequency was 40kHz, the treatment time was 5 hours, the temperature was 80°C, and then dried at 100°C for 6 hours. After the carbon fibers were chopped, they were soaked in a dopamine solution with a concentration of 3 g / L and a pH of 9. The reaction was stirred at room temperature for 24 hours, and then the carbon fibers were taken out, rinsed with deionized water, and dried at 80°C for 5 hours. Cellulose nanocrystals were dispersed in a solution containing 3% silane coupling agent, with an ultrasonic power of 500 W, and ultrasonically treated for 4 hours, then filtered and dried at 80°C for 5 hours.
[0117] The pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose are added to a high-speed mixer for primary ultrasonic mixing. During the primary ultrasonic mixing, the mixture is stirred and mixed at 80°C for 2 hours, and the stirring speed is initially 800 rpm and gradually increased to 1500 rpm. Then, flake graphite, nano molybdenum disulfide and whisker-like alumina are added to the mixture of the primary ultrasonic mixing in the high-speed mixer for secondary ultrasonic mixing. During the secondary ultrasonic mixing, the mixture is stirred and mixed for 2 hours at a stirring speed of 1800 rpm. Then, carbon fiber and cellulose nanocrystals are added to the mixture of the secondary ultrasonic mixing in the high-speed mixer for tertiary ultrasonic mixing. During the tertiary ultrasonic mixing, the mixture is stirred and mixed for 2 hours at a stirring speed of 2000 rpm.
[0118] The mixed powder is loaded into a mold, and a magnetic field with a magnetic field strength of 2 Tesla is applied around the mold. Pre-pressing is performed while applying the magnetic field, with a pressure of 300 MPa, a holding time of 10 seconds, and a pressing speed of 10 mm / s; the pre-pressed material is subjected to bidirectional pressing, with a pressure of 900 MPa, a holding time of 25 seconds, and a pressing speed of 8 mm / s. During the bidirectional pressing process, the mold is heated to 150°C at a heating rate of 25°C / min.
[0119] The formed material is placed in a vacuum of 1×10 -2Low-temperature pre-sintering was carried out under vacuum conditions of 1000°C, with a temperature of 1000°C, a time of 2 hours, and a heating rate of 20°C / minute; the pre-sintered material was placed in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering, with a hydrogen content of 12%, a sintering temperature of 1400°C, a sintering time of 3 hours, and a heating rate of 25°C / minute. During the high-temperature sintering process, microwave assisted sintering was adopted, with a microwave frequency of 2.45 GHz and a microwave power of 10 kW.
[0120] The sintered material was ground and polished using a low stress machining method with a grinding speed of 20 m / s and a feed rate of 0.15 mm / rev to achieve the required size and surface accuracy. The machined material was first phosphated at a temperature of 70°C for 30 minutes and a phosphating solution spray pressure of 0.3 MPa. The phosphating solution formula was 30 g / L zinc dihydrogen phosphate, 70 g / L zinc nitrate and 3 g / L sodium fluoride, with a pH value of 3. The phosphated material was electroplated with copper at a current density of 3A / dm² for 30 minutes. The material was heat treated under nitrogen protection, heated to 300°C at a heating rate of 20°C / min, kept at this temperature for 2 hours, and then slowly cooled to room temperature at a cooling rate of 10°C / min.
[0121] Comparative Example 1
[0122] Transmission plate material composition: 75% high-purity atomized iron powder, 15% electrolytic copper powder, 5% graphite powder, 3% zinc stearate and 2% nickel powder
[0123] Preparation method of transmission plate material:
[0124] High-purity atomized iron powder, electrolytic copper powder and nickel powder are mixed for 30 minutes using a stirring device at a stirring speed of 500 rpm. Graphite powder and zinc stearate are added and mixing is continued for 15 minutes. The mixed powder is directly loaded into a mold and pressed in one direction at a pressure of 400 MPa for 10 seconds. The powder is sintered in a sintering furnace at a sintering temperature of 1100°C for 3 hours. After sintering, the powder is ground at a grinding speed of 8 m / s and a feed rate of 0.2 mm / rev.
[0125] Comparative Example 2
[0126] The material components of the transmission plate are: 80% high-purity atomized iron powder, 10% electrolytic copper powder, 6% tungsten carbide powder, 2% ferrophosphorus powder and 2% paraffin.
[0127] Preparation method:
[0128] The high-purity atomized iron powder and electrolytic copper powder of the transmission plate material are mixed for 20 minutes at a stirring speed of 400 rpm. Tungsten carbide powder, ferrophosphorus powder and paraffin are added and mixed for another 10 minutes. After the powder is loaded into the mold, it is cold isostatically pressed at a pressure of 300 MPa. The sintering is carried out in a vacuum furnace with a vacuum degree of 1×10 -1 Pa, the sintering temperature is 1000℃, the time is 2.5 hours, and the material is polished by polishing method.
[0129] The following is a comparison table of the performance parameters of the transmission plate materials of Examples 1-6 and Comparative Examples 1 and 2:
[0130]
[0131] Through the above comparison, in terms of hardness, the high-purity atomized iron powder of the embodiment group as the main matrix component provides a certain basis for the hardness. At the same time, the addition of alloying elements such as molybdenum iron powder and chromium powder helps to improve the hardness of the material. Nano silicon carbide particles have high hardness characteristics and can effectively improve the overall hardness when evenly dispersed in the material. For example, the nano silicon carbide particle content in Example 4 and Example 6 is relatively high (3.5%), and the hardness values thereof reach 290.1HV and 295.8HV, respectively, which are relatively high. The presence of rare earth oxides can refine the grains and make the crystal structure denser. , and also has a positive effect on hardness. In the preparation method, the steps of ball milling of metal powder and pretreatment of nano-silicon carbide particles are conducive to uniform mixing and dispersion strengthening of each component, and further improve the hardness; Comparative Examples 1 and 2 use more traditional material formulations, lacking the synergistic effect of multiple high-performance additives such as in the embodiments. The content of high-purity atomized iron powder in Comparative Example 1 is too high, and other elements that enhance hardness are relatively small, and no special pretreatment and optimized preparation process have been performed, resulting in hardness of only 190.1HV and 203.5HV, which are much lower than those in the embodiments.
[0132] In terms of strength, the electrolytic copper powder and hydroxy nickel powder of the embodiment group form a good alloy system with the iron powder in the material, which enhances the strength of the material. The carbon fiber and whisker-like alumina have high strength and good bearing capacity, and play a role in reinforcing the skeleton inside the material. For example, the synergistic effect of the components in Example 6 is good, and the strength reaches 900.1MPa. During the preparation process, multi-step ultrasonic mixing makes the components mixed evenly, and the magnetic field-assisted molding and bidirectional pressing process can make the powder particles arranged more closely, improve the density of the material, thereby improving the strength. During the high-temperature sintering process, the diffusion and reaction between the components form a stable organizational structure, which also helps to improve the strength. The material in the comparative example does not have the rich alloy system and reinforcement combination in the embodiment. The iron powder content in the comparative example 2 is as high as 80%, and other reinforcement components are less and simple. At the same time, its preparation method, such as cold isostatic pressing and ordinary vacuum sintering process, cannot effectively improve the density and organizational structure uniformity of the material like the magnetic field-assisted molding and microwave-assisted sintering processes in the embodiments, so the strength is relatively low, which are 650.2MPa and 600.3MPa respectively.
[0133] In terms of friction coefficient, the flake graphite and nano-molybdenum disulfide in the embodiment group play a key role as lubricants in the material. They form a lubricating film on the friction surface and reduce the friction coefficient. In Example 3, Example 4 and Example 6, due to the optimized mixing process in the preparation process, the lubricant is evenly distributed in the material, and the friction coefficient is as low as 0.11, 0.10 and 0.09, respectively. The special structure of cellulose nanocrystals (0.8%) may also contribute to the adhesion of the lubricant and the improvement of friction performance to a certain extent. The comparative examples lack the optimized lubricant combination and uniform distribution process in the embodiments. Comparative Examples 1 and 2 mainly use simple graphite powder or paraffin as lubricants, and there is no multi-step ultrasonic mixing and other processes in the embodiments to ensure the uniform dispersion of the lubricant, resulting in a higher friction coefficient of 0.25 and 0.22, respectively, which is easy to generate greater friction during the friction process.
[0134] In terms of wear rate, the high hardness and good lubrication performance of the materials in the embodiment group work together to reduce the wear rate. The synergistic effect of components that increase hardness, such as nano silicon carbide particles, chromium powder, and lubricants such as flaky graphite and nano molybdenum disulfide, is significant. For example, in Example 4 and Example 6, the hardness is relatively high and the lubrication is good, and the wear rates are 0.45 mg / h and 0.41 mg / h, respectively, which are relatively low. The phosphating treatment in the preparation process can also improve the wear resistance of the material surface to a certain extent and reduce the wear rate. Due to the low hardness and poor lubrication, the wear rate of the control example is significantly higher than that of the embodiment. During the friction process, the material surface of Comparative Examples 1 and 2 is easily worn, and the wear rates reach 1.63 mg / h and 1.27 mg / h, respectively, because they lack the synergistic effect of multiple components and processes for enhancing hardness and improving lubrication in the embodiments.
[0135] In terms of thermal conductivity, the electrolytic copper powder of the embodiment group has good thermal conductivity, and its content is relatively stable in the embodiment, which provides a guarantee for the thermal conductivity of the material. At the same time, the uniform distribution and good bonding state of the components inside the material are also conducive to the conduction of heat. In Example 6, the mixing uniformity of the components is good, and the thermal conductivity reaches 88W / ( ), during the preparation process, the high temperature sintering process helps to improve the density of the material, thereby improving the thermal conductivity; the material formula and preparation process in the comparative example are not conducive to improving the thermal conductivity, the metal powders of comparative examples 1 and 2 have not been specially treated to improve their bonding performance, and the density of the material has not been improved by optimizing the process as in the embodiment, resulting in poor thermal conductivity, which is 60.1W / ( ) and 65.2W / ( ), heat conduction inside the material is easily hindered.
[0136] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0137] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0138] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0139] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.
[0140] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.
Claims
1. A powder metallurgy transmission plate material for a clutch, characterized in that: The transmission plate material comprises, by weight percentage, 55%-65% high-purity atomized iron powder, 8%-12% electrolytic copper powder, 4%-8% hydroxy nickel powder, 1.5%-4% ferromolybdenum powder, 1%-3% chromium powder, 0.3%-1.5% lanthanum powder, 1.5%-3.5% nano silicon carbide particles, 0.8%-2% carbon fiber, 0.5%-1.5% whisker-like aluminum oxide, 0.3%-1% cellulose nanocrystals, 0.5%-2% rare earth oxide, 2.3%-6% lubricant and 0.5%-1.8% binder; The rare earth oxides include 0.4%-1.6% of cerium oxide and 0.1%-0.4% of yttrium oxide.
2. The powder metallurgy transmission plate material for clutch according to claim 1, characterized in that: The lubricant comprises 1.5%-3.5% of flake graphite and 0.8%-2.5% of nano molybdenum disulfide.
3. The powder metallurgy transmission plate material for clutch according to claim 2, characterized in that: The binder comprises 0.3%-1% polyethylene glycol and 0.2%-0.8% sodium carboxymethyl cellulose.
4. A method for preparing a powder metallurgy transmission plate material for a clutch according to claim 3, characterized in that: The preparation method comprises: S1: Pretreatment of high purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, carbon fiber, cellulose nanocrystals; S2: adding the pretreated high-purity atomized iron powder, electrolytic copper powder, hydroxy nickel powder, molybdenum iron powder, chromium powder, lanthanum powder, nano silicon carbide particles, rare earth oxides, polyethylene glycol and sodium carboxymethyl cellulose into a high-speed mixer for primary mixing, then adding flake graphite, nano molybdenum disulfide and whisker-like aluminum oxide into the primary mixed mixture in the high-speed mixer for secondary mixing, then adding carbon fiber and cellulose nanocrystals into the secondary mixed mixture in the high-speed mixer for tertiary mixing; S3: molding the three-mixed mixture by bidirectional pressing; S4: performing low-temperature pre-sintering and high-temperature sintering on the formed material in sequence; S5: Machining, surface treatment and heat treatment of the sintered material.
5. The method for preparing a powder metallurgy transmission plate material for a clutch according to claim 4, characterized in that: Step S1 specifically includes: S11: vacuum drying the high-purity atomized iron powder, electrolytic copper powder, carbonyl nickel powder, ferromolybdenum powder, chromium powder and lanthanum powder respectively at a drying temperature of 110-130° C. for 5-7 hours; S12: soaking the nano-silicon carbide particles in a composite treatment agent of a silane coupling agent and a titanate coupling agent, stirring evenly and then performing ultrasonic treatment for 3-5 hours at a temperature of 60-80° C., and then drying at 80-100° C. for 4-6 hours; S13: After the carbon fiber is chopped, it is immersed in a dopamine solution, the concentration of the dopamine solution is 1-3 g / L, the pH value is 8-9, and the reaction is stirred at room temperature for 12-24 hours, and then the carbon fiber is taken out, rinsed with deionized water, and dried at 60-80° C. for 3-5 hours; S14: dispersing cellulose nanocrystals in a silane coupling agent, ultrasonically treating for 2-4 hours, and then filtering and drying.
6. The method for preparing a powder metallurgy transmission plate material for a clutch according to claim 4, characterized in that: In step S2, during the first mixing process, stirring and mixing are performed at 60-80°C for 1-2 hours, during the second mixing process, stirring and mixing are performed for 1-2 hours, and during the third mixing process, stirring and mixing are performed for 1-2 hours, wherein the first mixing, the second mixing and the third mixing are all combined with ultrasonic assisted mixing.
7. The method for preparing a powder metallurgy transmission plate material for a clutch according to claim 4, characterized in that: Step S3 specifically includes: S31: The mixed powder is loaded into a mold and pre-pressed at a pressure of 200-300 MPa, a holding time of 5-10 seconds, and a pressing speed of 5-10 mm / s; S32: The pre-pressed material is subjected to bidirectional pressing at a pressure of 600-900 MPa, a holding time of 15-25 seconds, and a pressing speed of 3-8 mm / s. During the bidirectional pressing process, the mold is heated to 100-150°C at a heating rate of 15-25°C / min.
8. The method for preparing a powder metallurgy transmission plate material for a clutch according to claim 4, characterized in that: Step S4 specifically includes: S41: The formed material is placed in a vacuum of 1×10 -3 -1×10 -2 Low temperature pre-sintering is carried out under vacuum conditions of 1000 Pa, the temperature is 800-1000°C, the time is 1-2 hours, and the heating rate is 10-20°C / min; S42: placing the pre-sintered material in a mixed atmosphere of nitrogen and hydrogen for high-temperature sintering at a temperature of 1200-1400°C for 2-3 hours at a heating rate of 15-25°C / minute, wherein microwave assisted sintering is adopted during the high-temperature sintering process, the microwave frequency is 2.45 GHz, and the microwave power is 5-10 kW.
9. The method for preparing a powder metallurgy transmission plate material for a clutch according to claim 4, characterized in that: Step S5 specifically includes: S51: Mechanical processing of the sintered material; S52: The machined material is first subjected to phosphating treatment at a temperature of 50-70°C for 20-30 minutes and a phosphating solution spraying pressure of 0.1-0.3MPa. The phosphating solution formula is: 20-30g / L zinc dihydrogen phosphate, 50-70g / L zinc nitrate and 1-3g / L sodium fluoride, with a pH value of 2-3; S53: electroplating copper or chemical copper plating is performed on the phosphating material. When electroplating copper is used, the current density is 1-3A / dm², the electroplating time is 10-30 minutes, and when chemical copper plating is used, the plating solution temperature is 40-60°C, and the deposition rate is 2-5μm / h; S54: heat-treating the material under nitrogen protection, heating to 200-300°C at a heating rate of 10-20°C / min, keeping the temperature for 1-2 hours, and then slowly cooling to room temperature at a cooling rate of 5-10°C / min.
Citation Information
Patent Citations
Alloy powder made of micro-nanometer particles through enhanced laser cladding and method for preparing same
CN103495737A
Process for obtaining tight components by powder metallurgy
CN105745044A